2016
DOI: 10.1007/s12070-016-1020-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined Expansion Pharyngoplasty and Anterior Palatoplasty for the Treatment of OSA

Abstract: To evaluate the success rates of combined Expansion Sphincter Pharyngoplasty and the Anterior Palatoplasty in the treatment of OSA. A two center prospective series of 73 patients with OSA. All patients were [18 years old, retro-palatal obstruction, concentric velo-pharyngeal collapse, BMI \ 33, Friedman clinical stage II, with all grades of AHI. The procedure involved the anterior palatoplasty, tonsillectomy and expansion sphincter pharyngoplasty with or without nasal surgery. There were 68 men and 5 women, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 20 publications
3
32
0
5
Order By: Relevance
“…Similar result for BP was reported by Montevecchi et al, as a decreasing in mean AHI from 33.4 to 13.5 . Recently, Pang et al reported the results of combined ESP and AP for OSA treatment and they showed a decrease in mean AHI from 26.3 to 12.6 …”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar result for BP was reported by Montevecchi et al, as a decreasing in mean AHI from 33.4 to 13.5 . Recently, Pang et al reported the results of combined ESP and AP for OSA treatment and they showed a decrease in mean AHI from 26.3 to 12.6 …”
Section: Introductionsupporting
confidence: 85%
“…Karakoc et al evaluated the outcomes of patients who were treated with the new surgical procedures in their prospective study and the success rates had been reported as 45% and 74% for AP and ESP, respectively . However, a combination of ESP and AP, had reported by Pang et al, gives better results for patients with OSA as the success rate of 83.2% . Our study showed 84.9% success rates for ESPwAP.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations